Inorganic reinforced polyamide resin composition
By blending specific ratios of crystalline and amorphous polyamides with inorganic reinforcement and modified polyolefin in the polyamide resin composition, the challenges of achieving high rigidity, toughness, and wear resistance are addressed, resulting in a versatile material for various applications.
Patent Information
- Application Number
- JP2021576006
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-10
- Filing Date
- 2021-06-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-06-24
AI Technical Summary
Existing inorganic reinforced polyamide resin compositions struggle to achieve a balance between high rigidity, toughness, and long-term wear resistance, especially when used as counter materials with other resin compositions, due to limitations in sliding properties and compatibility with lubricants.
The composition blends crystalline polyamide resin, amorphous polyamide, inorganic reinforcement such as glass fibers, and modified polyolefin resin with reactive functional groups, optimizing the mass ratios to enhance mechanical properties, flowability, and sliding performance.
This approach results in a highly rigid, tough, and sliding material with excellent long-term wear resistance, suitable for metal replacements and thin-walled molded products, particularly in electronic and automotive applications.
Smart Images

Figure 0007653083000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an inorganic reinforced polyamide resin composition having high rigidity and high toughness, and more particularly to an inorganic reinforced polyamide resin composition which has excellent long-term abrasion resistance when used in combination with a molded article made of a resin composition containing an inorganic reinforcement material. [Background technology]
[0002] Polyamide resins have excellent mechanical properties, heat resistance, impact resistance, and chemical resistance, and are widely used in automobile parts, electrical parts, electronic parts, household goods, etc. Among them, polyamide resins to which inorganic reinforcing materials, such as glass fibers, have been added have significantly improved rigidity, strength, and heat resistance, and it is known that the rigidity is improved in proportion to the amount of addition. Therefore, inorganic fiber-reinforced polyamide resin compositions are widely used as internal and external members in the electronic and electrical equipment and automotive fields. In recent years, the level of vibration characteristics required has been increasing, especially due to the thinning of product thickness in electronic and electrical components and the miniaturization of vehicle parts.
[0003] In addition to mechanical properties, polyamide resins also have excellent wear resistance, and are therefore widely used in sliding parts in various fields, including gears and cam bearings. In order to obtain better sliding properties, it is known to blend solid lubricants such as molybdenum disulfide, graphite, and fluororesins, and liquid lubricants such as various lubricating oils and silicone oils (for example, Non-Patent Document 1). However, among these sliding improvers, solid lubricants require blending in large amounts, which has the drawback of significantly reducing the toughness of the base polyamide resin. Although liquid lubricants can impart effective sliding properties with a relatively small amount, they often have poor compatibility with the base resin, and the surface of the molded product is often contaminated by these liquid lubricants, which has the drawback of limiting their use.
[0004] In addition, methods proposed to improve the drawbacks of blending various lubricants include blending a modified styrene copolymer with a modified high-density polyethylene having a specific range of molecular weight (Patent Document 1), and using a high-viscosity polyamide resin and blending it with modified polyethylene (Patent Document 2). The polyamide resin composition has made it possible to provide molded articles having excellent sliding properties without the above-mentioned drawbacks. These polyamide resins are highly effective in improving the sliding properties when the mating material is a metal. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Osamu Fukumoto, "Plastic Materials Lecture
[16] Polyamide Resin", Nikkan Kogyo Shimbun (1970) [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 8-157714 [Patent Document 2] WO2008 / 075699 publication Summary of the Invention [Problem to be solved by the invention]
[0007] However, in recent years, the trend of making molded products thinner and more complex in shape has led to a demand for materials with high rigidity and toughness, but no materials with sufficient mechanical properties have been developed to meet this demand. Furthermore, in recent years, as the weight of molded products has been reduced, the mating material has been changing from metal to the same resin. In order to increase the rigidity, if a large amount of inorganic reinforcing material is filled into these polyamide resins, a problem occurs in which the mating material is scraped off by the inorganic reinforcing material present on the surface. As a result, it has not been possible to obtain a material that satisfies both high rigidity and high sliding properties.
[0008] The present invention has been devised in view of the above-mentioned current state of the prior art, and an object of the present invention is to provide an inorganic reinforced polyamide resin composition which has both the contradictory mechanical properties of high rigidity and impact resistance (high toughness), has excellent fluidity, and further has excellent long-term abrasion resistance (high sliding) when used with an inorganic fiber reinforced material as a sliding mating material. [Means for solving the problem]
[0009] The inventors focused on the fact that, when inorganic reinforced polyamide resins slide against each other, the amount of wear is determined by the amount of inorganic reinforcing material precipitated on the surface of the molded article, and even more significantly, by the amount of the end faces and fracture surfaces of the inorganic reinforcing material protruding from the surface, and that the brittleness of the resin part caused by an increase in the amount of inorganic reinforcing material is a dominant factor, and as a result of extensive research to achieve the above-mentioned object, they found that all of the above-mentioned objects can be solved by blending amorphous polyamide and modified polyolefin in an inorganic reinforced polyamide resin composition in a balanced manner from various perspectives, which led to the completion of the present invention.
[0010] That is, the present invention has the following configuration. [1] An inorganic reinforced polyamide resin composition comprising 10 to 55 mass% of a crystalline polyamide resin (A), 1 to 20 mass% of an amorphous polyamide resin (B), 40 to 70 mass% of an inorganic reinforcing material (C), and 0.5 to 10 mass% of a modified polyolefin resin (D) having a reactive functional group capable of reacting with an end group and / or a main chain amide group of the polyamide resin, An inorganic reinforced polyamide resin composition, characterized in that the blending mass ratio of component (A) to component (D) satisfies 0.01≦(D) / (A)≦0.2, and the blending mass ratio of component (A) to component (B) satisfies 0.05≦(B) / (A)≦0.7. [2] The inorganic reinforced polyamide resin composition according to [1], characterized in that the crystalline polyamide resin (A) comprises a crystalline polyamide resin (A1) and a crystalline polyamide resin (A2) having a melting point 20°C or more higher than that of the crystalline polyamide resin (A1), and the blending mass ratio of the (A1) component to the (A2) component is 0.1≦(A2) / (A1)≦0.5. [3] The inorganic reinforced polyamide resin composition according to either [1] or [2], wherein the modified polyolefin resin (D) is a modified polyethylene resin. [4] The inorganic reinforced polyamide resin composition according to any one of [1] to [3], wherein the inorganic reinforcing material (C) is glass fiber having a number average fiber length of 140 μm or more. Effect of the Invention
[0011] The polyamide resin composition of the present invention achieves both the contradictory mechanical properties of high rigidity and impact resistance and can therefore be used as a metal replacement or for thin-walled molded articles. In addition, it has excellent flowability and is a high-rigidity, high-sliding material that exhibits excellent long-term abrasion resistance when used with an inorganic fiber reinforced material as the mating material. Therefore, the inorganic reinforced polyamide resin composition and its molded articles that can be used as a metal replacement can be easily produced, making it possible to realize unprecedented downsizing in vehicle parts used in housings for electronic and electrical parts and in the interior and exterior of automobiles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The inorganic reinforced polyamide resin composition of the present invention will be described in detail below.
[0013] The crystalline polyamide resin (A) in the present invention is not particularly limited as long as it is a polymer having an amide bond (-NHCO-) in the main chain and is crystalline. Examples of the crystalline polyamide resin (A) include polyamide 6 (NY6), polyamide 66 (NY66), polyamide 46 (NY46), polyamide 11 (NY11), polyamide 12 (NY12), polyamide 610 (NY610), polyamide 612 (NY612), polymetaxylylene adipamide (MXD6), hexamethylenediamine-terephthalic acid polymer (6T), hexamethylenediamine-terephthalic acid and adipic acid polymer (6T / 66), hexamethylenediamine-terephthalic acid and adipic acid polymer (6T / 66), and the like. Examples of the polyamide resin include crystalline polyamide resins such as hexamethylenediamine-terephthalic acid and ε-caprolactam copolymer (6T / 6), trimethylhexamethylenediamine-terephthalic acid polymer (TMD-T), metaxylylenediamine, adipic acid and isophthalic acid copolymer (MXD-6 / I), trihexamethylenediamine, terephthalic acid and ε-caprolactam copolymer (TMD-T / 6), diaminodicyclohexylenemethane (CA), isophthalic acid and lauryllactam copolymer, and blends thereof, but are not limited thereto. In the present invention, aliphatic polyamides are preferred, and polyamide 6 and polyamide 66 are more preferred. Alternatively, when two types of polyamides are used, it is preferred to use polyamides having melting points different by 20°C or more from the viewpoint of controlling the solidification rate. Furthermore, the crystalline polyamide resin (A) contains a crystalline polyamide resin (A1) and a crystalline polyamide resin (A2) having a melting point 20° C. or more higher than that of the crystalline polyamide resin (A1), and the blending ratio of the (A1) component to the (A2) component is more preferably 0.1≦(A2) / (A1)≦0.5. In one preferred embodiment, the crystalline polyamide resin (A1) is polyamide 6, and the crystalline polyamide resin (A2) is polyamide 66.
[0014] The relative viscosity of the crystalline polyamide resin (A) in the present invention is not particularly limited, but can be in the range of 1.5 to 3.5, measured in a 96% sulfuric acid solution (polyamide resin concentration 1 g / dl, temperature 25°C). It is preferably 1.5 to 3.3. More preferably 1.5 to 2.8. If it is in this range, even if the resin composition is highly filled with inorganic reinforcing material, it can be given a flowability suitable for injection molding, and molding of small / thin molded products is possible, and the toughness as a resin is also satisfactory. To obtain a polyamide resin with a relative viscosity of 1.5 to 3.5, there is a method of polymerizing a polyamide resin with a relative viscosity of 1.8 to 3.5 by adjusting the production conditions, or after producing a polyamide resin with a relative viscosity of more than 3.5, cutting the polyamide molecular chain using a viscosity reducer. As the viscosity reducing agent, aliphatic dicarboxylic acids, aromatic dicarboxylic acids, etc. are effective, and specific examples include oxalic acid, malonic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, phthalic acid, terephthalic acid, etc. The amount of the agent added can be about 0.1 to 3 parts by mass per 100 parts by mass of the polyamide resin, and the agent can be obtained by blending and melt-kneading.
[0015] The content of the crystalline polyamide resin (A) in the polyamide resin composition of the present invention is from 10 to 55% by mass, preferably from 15 to 45% by mass, and more preferably from 20 to 40% by mass.
[0016] The amorphous polyamide resin (B) used in the present invention does not show a clear melting point when measured by a differential scanning calorimeter (DSC) in accordance with JIS K7121.
[0017] Specific examples of monomers constituting the amorphous polyamide resin (B) include bis(4-aminocyclohexyl)methane (sometimes abbreviated as PACM), bis(3-aminocyclohexyl)methane, bis(3-methyl-4-aminocyclohexyl)methane (sometimes abbreviated as MACM), 2,2-bis(4-aminocyclohexyl)propane, isophoronediamine, tetramethylenediamine, hexamethylenediamine, undecamethylenediamine, dodecamethylenediamine, 2,2,4 / 2,4,4-trimethylhexamethylenediamine (TMD), 5-methylnonamethylenediamine, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, and the like. Examples of the diamines include diamines such as hexane, 3-aminocyclohexyl-4-aminocyclohexylmethane, 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, bis(aminopropyl)piperazine, and bis(aminoethyl)piperazine. Examples of the dicarboxylic acids include adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid (sometimes abbreviated as 12), tridecanedioic acid, and tetradecanedioic acid (sometimes abbreviated as 14), and other aliphatic dicarboxylic acids having linear or alkyl side chains with 4 to 36 carbon atoms, and aromatic dicarboxylic acids such as terephthalic acid (sometimes abbreviated as T) and isophthalic acid (sometimes abbreviated as I). Examples of the aminocarboxylic acids include lactams such as ε-caprolactam and ω-laurolactam (LL), and aminocarboxylic acids such as 6-aminocaproic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid.
[0018] Preferred examples of the combination of monomers include combinations of alicyclic diamines such as bis(4-aminocyclohexyl)methane (PACM), bis(3-aminocyclohexyl)methane, bis(3-methyl-4-aminocyclohexyl)methane (MACM), and 2,2-bis(4-aminocyclohexyl)propane with dicarboxylic acids such as undecanedioic acid, dodecanedioic acid, tridecanedioic acid, and tetradecanedioic acid. Specific examples include polymers, copolymers, and blends of 12MACM, 14MACM, 10MACM / 11, 12MACM / I, I / MACM / LL, T / TMD, and 6T6I, but are not limited thereto. For example, when the crystalline polyamide resin (A) is polyamide 6, 6T6I is preferred.
[0019] The relative viscosity (96% sulfuric acid method) of the amorphous polyamide resin is not particularly limited, but is preferably in the range of 1.8 to 2.4, and more preferably in the range of 1.9 to 2.2.
[0020] The content of the amorphous polyamide resin (B) in the polyamide resin composition of the present invention is 1 to 20% by mass. If the amount of the amorphous polyamide resin (B) is less than 1% by mass, the cooling and solidification speed in the mold becomes too fast, causing severe appearance defects such as filler lift and flow marks, and also deteriorating abrasion resistance. On the other hand, if the amount of the amorphous polyamide resin (B) exceeds 20% by mass, the cooling and solidifying speed becomes too slow, resulting in poor releasability, adhesion to the mold and failure to release, or wrinkles on the surface of the molded product. Furthermore, the crystallinity becomes too poor, which may lead to a decrease in mechanical strength and impact strength. The content of the amorphous polyamide resin (B) is preferably 2 to 15% by mass, more preferably 3 to 10% by mass.
[0021] In the present invention, the mass ratio of the component (A) to the component (B) must satisfy the following formula: 0.05≦(B) / (A)≦0.7 In the present invention, when (B) / (A) is within this range, a molded article with a higher level of excellent appearance can be obtained, and (B) / (A) is preferably 0.08 or more and 0.4 or less, and more preferably 0.10 or more and 0.2 or less.
[0022] The inorganic reinforcing material (C) in the present invention is one that most effectively improves physical properties such as strength, rigidity, and heat resistance, and specifically includes fibrous materials such as glass fibers, carbon fibers, alumina fibers, silicon carbide fibers, and zirconia fibers, whiskers such as aluminum borate and potassium titanate, acicular wollastonite, milled fibers, etc. In addition to these, glass beads, glass flakes, glass balloons, silica, talc, kaolin, wollastonite, mica, alumina, hydrotalcite, montmorillonite, graphite, carbon nanotubes, fullerenes, zinc oxide, indium oxide, tin oxide, iron oxide, titanium oxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, red phosphorus, calcium carbonate, potassium titanate, lead zirconate titanate, barium titanate, aluminum nitride, boron nitride, zinc borate, aluminum borate, barium sulfate, magnesium sulfate, layered silicates that have been organically treated for the purpose of delamination, and other fillers can also be used as the inorganic reinforcing material (C). Among these, glass fiber, carbon fiber, etc. are particularly preferably used. These inorganic reinforcing materials (C) may be used alone or in combination of two or more kinds.
[0023] When a fibrous reinforcing material is used as the inorganic reinforcing material (C), among the above, glass fiber, carbon fiber, etc. are particularly preferably used. These fibrous reinforcing materials are preferably pretreated with a coupling agent such as an organic silane compound, an organic titanium compound, an organic borane compound, and an epoxy compound, and are particularly preferably those that react easily with a carboxylic acid group or / and a carboxylic anhydride group. Polyamide resin compositions containing glass fibers treated with a coupling agent are preferred because they can provide molded products with excellent mechanical properties and appearance properties. In addition, other fibrous reinforcing materials can also be used by adding a coupling agent after the untreated material is used.
[0024] When the inorganic reinforcing material (C) is glass fiber, chopped strands cut to a fiber length of about 1 to 20 mm can be preferably used. Glass fibers having a circular or noncircular cross section can be used as the cross section of the glass fiber. From the viewpoint of physical properties, glass fibers having a noncircular cross section are preferred. Glass fibers having a noncircular cross section include those having a substantially elliptical, substantially oval, or substantially cocoon-shaped cross section perpendicular to the longitudinal direction of the fiber, and the flatness is preferably 1.5 to 8. The flatness here is the ratio of the major axis to the minor axis when a rectangle having the minimum area circumscribing the cross section perpendicular to the longitudinal direction of the glass fiber is assumed, and the length of the long side of this rectangle is the major axis and the length of the short side is the minor axis. The thickness of the glass fiber is not particularly limited, but the minor axis is about 1 to 20 μm and the major axis is about 2 to 100 μm.
[0025] The number average fiber length of the glass fibers in the polyamide resin composition of the present invention is preferably 140 to 700 μm, more preferably 180 to 400 μm. The glass fiber length in this range provides high strength, high rigidity, and stable flowability. If the glass fibers are outside the above range, it becomes difficult to orient and fill the polyamide resin surface, and the fiber end faces may be exposed on the surface, resulting in reduced abrasion resistance.
[0026] The glass fibers are preferably treated with a coupling agent such as a silane or titanate type, and in particular, those treated with a silane type coupling agent are preferably used. Examples of preferred silane coupling agents include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-anilinopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane. In particular, γ-glycidoxypropyltrimethoxysilane, γ-anilinopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane are preferred.
[0027] The amount of inorganic reinforcing material (C) is 40-70% by mass, preferably 45-67% by mass, more preferably 50-65% by mass, and further preferably 55-65% by mass, based on 100% by mass of the total resin composition. If the amount exceeds 70% by mass, the productivity is deteriorated. If the amount is less than 40% by mass, the effect of the reinforcing material may not be fully exerted.
[0028] As fillers other than the inorganic reinforcing material (C), conductive fillers, magnetic fillers, flame-retardant fillers, and thermally conductive fillers can be used for different purposes other than reinforcing fillers. Specific examples include glass beads, glass flakes, glass balloons, silica, talc, kaolin, wollastonite, mica, alumina, hydrotalcite, montmorillonite, hydroxyapatite, graphite, carbon nanotubes, fullerenes, zinc oxide, indium oxide, tin oxide, iron oxide, titanium oxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, red phosphorus, calcium carbonate, potassium titanate, lead zirconate titanate, barium titanate, aluminum nitride, boron nitride, zinc borate, aluminum borate, barium sulfate, magnesium sulfate, zinc sulfide, iron, aluminum, copper, and silver. These fillers may be used alone or in combination of several types. The shape is not particularly limited, but needle-shaped, spherical, plate-shaped, and amorphous shapes can be used.
[0029] The modified polyolefin resin (D) in the present invention is a modified polyolefin resin such as the following. That is, olefin resins such as high density polyethylene, low density polyethylene, ultra-high molecular weight polyethylene, linear low density polyethylene, polypropylene, poly(1-butene), and poly(4-methylpentene) can be mentioned. From the viewpoint of abrasion resistance, high density polyethylene is the most preferable among these polyolefin resins. The number average molecular weight of the modified polyolefin resin (D) is preferably 50,000 to 400,000.
[0030] In the present invention, the high density polyethylene before modification is a polyethylene having a number average molecular weight of 50,000 to 400,000 and a density of 0.94 kg / cm 2 If the number average molecular weight is less than 50,000, the abrasion resistance of the resulting molded product will be insufficient, and if the molecular weight exceeds 400,000, molding will become difficult, which is undesirable.
[0031] The high-density polyethylene in the present invention may be copolymerized with other monomers, for example, α-olefins such as propylene, butene-1, pentene, 4-methylpentene-1, hexene, octene, decene, etc., dienes such as butadiene, isoprene, etc., cycloolefins such as cyclopentene, cyclohexene, cyclopentadiene, etc., and acrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, etc., within the range that does not impair the properties of the high-density polyethylene.
[0032] In order to improve compatibility with polyamide resins, the modified polyolefin resin (D) has a reactive functional group capable of reacting with the terminal group and / or main chain amide group of the polyamide resin. Specific examples of the functional group capable of reacting with polyamide resins include carboxylic acid groups, acid anhydride groups, epoxy groups, oxadrine groups, amino groups, isocyanate groups, etc., among which acid anhydride groups are particularly preferred due to their high reactivity with polyamide resins, and maleic anhydride is particularly preferred.
[0033] The amount of the modified polyolefin resin (D) is 0.1 to 10% by mass, preferably 0.5 to 7% by mass, and more preferably 1 to 5% by mass, in the total resin composition. When the modified polyolefin resin (D) is appropriately blended, a coating layer made of a tough modified polyolefin is formed on the outermost surface of the molded article by friction during sliding, and brittle wear of the polyamide is suppressed, thereby preventing the inorganic fiber reinforcement from protruding from the surface layer. The melting point of the modified polyolefin is preferably lower than that of the polyamide resins (A) and (B). This is because the modified polyolefin melts before the polyamide resin due to frictional heat and is likely to form a surface coating layer. If the polyamide resin is less than 0.1% by mass from the polyamide resin composition, a coating layer of sufficient thickness cannot be formed, and the effect of improving the wear resistance is reduced. If it is more than 10% by mass, the concentration of the modified olefin resin in the surface layer increases, reducing the surface layer hardness and increasing the friction coefficient. Furthermore, the mechanical properties of the inorganic reinforced polyamide resin composition are reduced.
[0034] In the present invention, the mass ratio of the component (A) to the component (D) must satisfy the following formula: 0.01≦(D) / (A)≦0.2 (D) / (A) is preferably 0.03 to 0.18, more preferably 0.04 to 0.15, and even more preferably 0.05 to 0.12. If (D) / (A) is 0.01 or less, a coating layer of sufficient thickness cannot be formed, and the effect of improving abrasion resistance is reduced. If it exceeds 0.2, the concentration of the modified olefin resin in the surface layer becomes high, which reduces the hardness of the surface layer and increases the coefficient of friction, and further deteriorates the mechanical properties of the inorganic reinforced polyamide resin composition.
[0035] The inorganic reinforced polyamide resin composition of the present invention preferably has a cooling crystallization temperature (TC2) measured by a differential scanning calorimeter (DSC) of 170° C.≦(TC2)≦190° C. The cooling crystallization temperature (TC2) is a peak temperature obtained by using a differential scanning calorimeter (DSC) to raise the temperature to 300° C. at a heating rate of 20° C. / min under a nitrogen stream, hold the temperature for 5 minutes, and then lower the temperature to 100° C. at a rate of 10° C. / min.
[0036] Furthermore, when the cooling crystallization temperature (TC2) does not satisfy 170°C≦(TC2)≦190°C, a higher level of good molded article appearance may not be obtained due to the crystallization rate of the polyamide resin composition.
[0037] If necessary, the inorganic reinforced polyamide resin composition of the present invention may contain heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, plasticizers, lubricants, crystal nucleating agents, release agents, antistatic agents, flame retardants, pigments, dyes, other polymers, etc. The inorganic reinforced polyamide resin composition of the present invention preferably contains the above-mentioned components (A), (B), (C) and (D) in total at 90% by mass or more, more preferably at 95% by mass or more.
[0038] The method for producing the polyamide resin composition of the present invention is not particularly limited as long as it is a melt kneading extrusion method that can accurately control the blending amounts of each component in the present invention within the above-mentioned specified ranges, but it is preferable to use a single screw extruder or a twin screw extruder.
[0039] When resin pellets to be mixed which are significantly different in shape, apparent specific gravity, friction coefficient, etc., are charged from the hopper of the extruder, it is preferable to employ the following method. That is, in this manufacturing method, a crystalline polyamide resin (A), an amorphous polyamide resin (B), and a modified polyolefin resin (D) are mixed in advance and fed into the hopper of an extruder, and an inorganic reinforcing material (C) is then fed by a side feed method. EXAMPLES
[0040] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. The raw materials used in the examples and comparative examples of the present invention are as follows.
[0041] (A) Crystalline polyamide resin A1: Polyamide 6: Toyobo "T-860" (RV2.0), melting point 225°C A2: Polyamide 66...Toray "CM3000EF" (RV2.4) Melting point 265℃ (B) Amorphous polyamide resin B: Polyamide 6T6I...EMS "Grivory G21" (RV2.0) (C) Inorganic reinforcement C: Glass fiber: Nippon Electric Glass Co., Ltd. "ECS03T-275H" (D): Modified polyolefin D1: Maleic anhydride modified polyethylene...Mitsubishi Chemical "Modic DH0200" D2: Maleic anhydride modified polypropylene... Prime Polymer "MMP-006" D3: Unmodified polyethylene... Prime Polymer "6203B" (E) Other additives Release agent: Calcium montanate... "CS-6CP" manufactured by Nitto Kasei Kogyo Stabilizer: Cupric bromide
[0042] The various evaluation methods are as follows. The evaluation results are shown in Table 1.
[0043] (1) Relative Viscosity (RV) of Polyamide Resin (96% Sulfuric Acid Solution Method) The viscosity was measured using an Ubbelohde viscosity tube at 25° C. in a 96% by weight sulfuric acid solution with a polyamide resin concentration of 1 g / dL.
[0044] (2) Melting point of polyamide resin The endothermic peak temperature was determined by measuring at a temperature rise rate of 20° C. / min using a differential scanning calorimeter (EXSTAR 6000, manufactured by Seiko Instruments Inc.).
[0045] (4)Melt index (MFR): Measured according to ISO1133. Measurement temperature: 275℃, load: 5kg
[0046] (5) Bending strength Measured in accordance with ISO178. (6) Charpy impact resistance Measurements were performed in accordance with ISO179-1.
[0047] (7) Number average fiber length The length of the remaining glass fibers in the pellets was measured by the following method. In highly glass fiber filled materials, there is a lot of interference between the glass fibers, which makes the glass fibers easily damaged during measurement and makes it difficult to determine the accurate fiber length. Therefore, in the present invention, in order to accurately measure the glass fiber length, the pellets obtained by melt kneading are ignited at 650°C for 2 hours, and the glass fibers are extracted as ash without damaging the glass fibers. The obtained glass fibers are immersed in water, and the dispersed glass fibers are placed on a preparation. More than 1,000 randomly selected glass fibers are observed at 80x magnification with a digital microscope (KH-7700, manufactured by Hirox Corporation) to determine the number average fiber length.
[0048] (8) Wear characteristics Using a thrust type abrasion tester, a flat plate (size: 50 mm × 50 mm) of a polyamide resin composition obtained by injection molding and a cylindrical molded product (outer diameter 20 mm, inner diameter 14.4 mm, contact area 1.51 cm) of the same material as the flat plate were subjected to abrasion testing. 2 ) for 60 minutes under a load of 55.5kgf / cm 2 The plates were then subjected to continuous sliding at a speed of 5 cm / sec. The amount of wear per unit distance (mg / km) was calculated from the difference in mass between the plate and the cylindrical molded product before and after abrasion and the total abrasion distance, and the dynamic friction coefficient was calculated from the converged load value during the abrasion test.
[0049] (9) Evaluation method for molded product appearance: The appearance of the molded product was evaluated by measuring the specular gloss by the following method. Using a mirror-finished mold measuring 100mm x 100mm x 3mm (thickness), molded products were produced at a resin temperature of 280°C and a mold temperature of 80°C, and the gloss was measured at an incidence angle of 60 degrees in accordance with JIS Z-8714. (The higher the value, the better the gloss.) The gloss measurement results were evaluated based on the following criteria. ◎: 97 or higher ○: 95 or more, less than 97 △: 90 or more, less than 95 ×: Less than 90
[0050] Examples 1 to 5, 7, Comparative Examples 1 to 6 The copper compound was prepared by preparing an aqueous solution of cupric bromide. The raw materials other than the inorganic reinforcing material were mixed in advance to obtain the composition shown in Table 1, and the mixture was fed from the hopper of a twin-screw extruder (TEM-75SS, Shibaura Machine Co., Ltd.) equipped with a main feeder (hopper section) in the first barrel from the upstream side of the extruder, a first side feeder in the fourth barrel, and a second side feeder in the eighth barrel. The inorganic reinforcing material was fed from the second side feeder of the twin-screw extruder. Compounding was carried out at a cylinder temperature of 280°C and a screw rotation speed of 180 rpm to prepare pellets. The obtained pellets were dried in a hot air dryer until the moisture content was 0.05% or less, and then various properties were evaluated. The evaluation results are shown in Table 1.
[0051] Example 6 Except for feeding the inorganic reinforcing material from the first side feeder of the twin-screw extruder, compounding was carried out in the same manner as in Example 1 to prepare pellets. The obtained pellets were dried in a hot air dryer until the moisture content was 0.05% or less, and then various properties were evaluated. The evaluation results are shown in Table 1.
[0052] [Table 1]
[0053] As is clear from the results in Table 1, Examples 1 to 7 within the scope of the present invention have a good balance between mechanical properties and abrasion resistance at high levels. On the other hand, Comparative Examples 1 and 2, which do not contain modified polyolefin or amorphous polyamide resin, have poor molded appearance in addition to poor abrasion resistance. Comparative Example 3, where (D) / (A) is outside the range, has deteriorated mechanical properties, and Comparative Example 4, where (B) / (A) is outside the range, has deteriorated molded product appearance, such as noticeable glass lifting, and also has low abrasion resistance. [Industrial Applicability]
[0054] The polyamide resin composition of the present invention achieves both the contradictory mechanical properties of high rigidity and impact resistance, and can therefore be used as a metal replacement or for thin-walled molded articles. In addition, the composition is a high-rigidity, high-sliding material that has excellent flowability and excellent long-term abrasion resistance when used with a molded article made of a resin composition containing an inorganic fiber reinforcement material. Therefore, the composition can be easily produced as an inorganic reinforced polyamide resin composition capable of replacing metal and used for high-sliding parts in a wide range of applications. This makes it extremely useful, since it allows for unprecedented downsizing to be achieved in the housings of electronic and electrical parts, and in vehicle parts used in the interior and exterior of automobiles.
Claims
1. An inorganic reinforced polyamide resin composition comprising 10 to 55 mass% of a crystalline polyamide resin (A), 1 to 20 mass% of an amorphous polyamide resin (B), 40 to 70 mass% of an inorganic reinforcing material (C), and 0.5 to 10 mass% of a modified polyolefin resin (D) having a reactive functional group capable of reacting with an end group and / or a main chain amide group of the polyamide resin, the blending mass ratio of the (A) component to the (D) component satisfies 0.01≦(D) / (A)≦0.2, and the blending mass ratio of the (A) component to the (B) component satisfies 0.05≦(B) / (A)≦0.7; and The inorganic reinforced polyamide resin composition is characterized in that the crystalline polyamide resin (A) comprises a crystalline polyamide resin (A1) and a crystalline polyamide resin (A2) having a melting point 20°C or more higher than that of the crystalline polyamide resin (A1), and the blending mass ratio of the (A1) component to the (A2) component is 0.1≦(A2) / (A1)≦0.
5.
2. 2. The inorganic reinforced polyamide resin composition according to claim 1, wherein the modified polyolefin resin (D) is a modified polyethylene resin.
3. 3. The inorganic reinforced polyamide resin composition according to claim 1, wherein the inorganic reinforcing material (C) is glass fiber having a number average fiber length of 140 μm or more.
Citation Information
Patent Citations
Resin composition for reflow soldering
JP1993051529A
Polyamide resin molding
JP1996157714A
Polyamide resin composition and self-tapping component made therefrom
JP2000248172A
Polyamide resin composition
JP2005162775A
Polyamide resin composition
JP2005239800A